Teaching with technology - Desberg, Peter; Fisher, Farah (North America : Allyn and Bacon, 1998)
This interactive CD-ROM'book' gives you a hands-on opportunity to learn about using technology in the classroom. It offers all the content of a traditional textbook for the computers in education course taught interactively, plus the ability to experience software just the way you'll encounter it on the job-word processing, spreadsheets, databases, multimedia, evaluation programs and more
System requirements: Windows 3.1, Windows for Workgroups 3.11 or Windows 95, 16 MB RAM, SVGA monitor, CD-ROM drive (2X)
Keywords: Educational technology; Teaching -- Aids and devices; Educational innovations